KINERJA TUTOR DALAM PROSES PEMBELAJARAN PAKET C - Lambok Amran Adrianto (JIV-Jurnal Ilmiah Visi, 2010)
The purpose of this research is to obtain empirical data on tutorâ€™s performance in managing instructional activities of Package C Program at Community Learning Activities Center (CLAC). The research was conducted at a CLAC in North Jakarta. The method employed was descriptive method with qualitative approach. The researcher made direct observation to the CLAC where Package C program was being implemented. To obtain valid and reliable data and information, the researcher also conducted in-depth interview. Based on the available data and information, the research concluded that according to the respondentsâ€™ opinion all tutors have conducted instructional process in the line with the existing standard procedures. The tutors make a good preparation before instructional process and they are capable enough to perform their tasks professionally. They have a good mastery of the instructional materials and sound ability to use appropriate instructional media to improve participantsâ€™ learning achievement. For a better result in the future, the tutors are suggested to be more proactive to develop their knowledge and skills related to their job.